2021
DOI: 10.1590/1806-9282.20210491
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of shear wave elastography in predicting preeclampsia in the first trimester

Abstract: OBJECTIVE: This study aimed to investigate the predictive value of shear wave elastography (SWE) for preeclampsia (PE) in first-trimester pregnancies.METHODS: Singleton pregnant women aged 18-45 years, who underwent routine first-trimester prenatal examinations (11-13 weeks+6 days) were enrolled. Pregnancies with anterior placenta and normal first-trimester screening test results were included in the study group.The SWE measurements of six areas of the placenta were performed, and the mean value was estimated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…This meta-study included a total of nine studies taken from seven articles for evaluation [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The basic characteristics of all included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This meta-study included a total of nine studies taken from seven articles for evaluation [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The basic characteristics of all included studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the other studies excluded placentas located in the posterior wall, except for Hefeda et al [ 30 ], who did not specify any restrictions on the placental position. Additionally, except for Sirinoglu et al [ 26 ], who specifically included women in early pregnancy, the other studies focused on mid-term and late-term pregnant women. The characteristics of the ultrasound elastography in the included studies are summarised in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In addition, several studies have used SWE techniques to compare placental stiffness in patients with preeclampsia and healthy pregnant women in the same trimester of pregnancy and found significant differences in stiffness between the two groups. [29][30][31] Fujita found that placental stiffness as determined using the SWE technique has a sensitivity and specificity of 92.3% and 91.3%, respectively, for diagnosing preeclampsia. Furthermore, the placental stiffness was also significantly higher in patients with high risk factors who were not preeclamptic than that in those without high risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The placental stiffness measured using ultrasound elastography is considered an indirect indicator of placental function and a potential biomarker for placental‐mediated disease 28 . In addition, several studies have used SWE techniques to compare placental stiffness in patients with preeclampsia and healthy pregnant women in the same trimester of pregnancy and found significant differences in stiffness between the two groups 29–31 . Fujita found that placental stiffness as determined using the SWE technique has a sensitivity and specificity of 92.3% and 91.3%, respectively, for diagnosing preeclampsia.…”
Section: Introductionmentioning
confidence: 99%